Investigation into the suitability of screen printed graphene-melanin pH sensors for use in bacterial culturing applications - Whelan, Simon Peter (2022)
Screen printed pH sensors have been developed that utilise conductive carbon/graphene coated with DMSO-melanin for pH sensitivity. Their effectiveness has been demonstrated in buffer solutions and here they have been tested in a mixture of various frequently used culturing media solutions along side live bacteria in order to assess their suitability for monitoring the pH in real world bacterial culturing applications. The results indicate that these sensors can be used to accurately and consistently determine the pH of culturing media solutions at a high sensitivity in the presence of bacterial growth over the biologically relevant range of pH5 to pH8. This sensitivity was consistent between different types of culturing media that the sensor was tested with (brain heart infusion, nutrient and lysogeny broth) as well as pH reference buffer solutions. Therefore based on these findings it can be concluded that this sensor is sufficiently robust and has the potential to be useful in applications such as monitoring the ambient conditions of cultured microorganisms in a bioreactor.